Development of an Eco-Friendly Method for Iron Extraction and Determination in Pharmaceuticals Using Ciprofloxacin Drug as Chelating agent (Baghdad Science Journal, 2016)
A method is developed for the determination of iron (III) in pharmaceutical preparations by coupling cloud point extraction (CPE) and UV-Vis spectrophotometry. The method is based on the reaction of Fe(III) with excess drug ciprofloxacin (CIPRO) in dilute H2SO4, forming a hydrophobic Fe(III)- CIPRO complex which can be extracted into a non-ionic surfactant Triton X-114, and iron ions are determined spectrophotometrically at absorption maximum of 437 nm. Several variables which impact on the extraction and determination of Fe (III) are optimized in order to maximize the extraction efficiency and improve the sensitivity of the method. The interferences study is also considered to check the accuracy of the procedure. The results have shown that the preconcentration factor of 71 fold leading to obtain a limit of detection of 2.67 ng mL-1 with linear calibration range of 5-150 ng mL-1 (r=0.9998) and a superb sensitivity in terms of molar absorptivity of 1.13x106 L.mol-1.cm-1 . The mean percent recovery of 99.78±0.53% and the precision (RSD %) ranged from 1.96 to 0.76 are achieved. The developed method is applied to the determination of iron in four selected pharmaceutical drugs. The experimental values agree statistically with the quoted values stated by the manufacturer’ companies.